International Health Telecommunications Project: Computer Mediated Communications and the Library - Ridley, Michael; Alger, Elizabeth; Neufeld, Vic; MacDonald, Peter; Jones, April (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see PDF